Approximate controllability of neutral functional differential system with unbounded delay - Jong Yeoul Park; Sang Nam Kang (International Journal of Mathematics and Mathematical Sciences)
We consider a class of control systems governed by the neutral functional differential equation with unbounded delay and study the approximate controllability of the system. An example is given to illustrate the result.